The Correlation between Community Behavior in Mosquito Habitat Control and the Existence of Larva Aedes aegypti in Dwikora, Medan Helvetia District - Tarigan, Yenni Gustiani; Hartati, Siti (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Background: The number of larva free index in Dwikora in 2016 was >43.5% which is still far below national standard, i.e., 95% with some dengue hemorrhagic fever (DHF) case obtained over the last two years was 16 cases. The study objective was to determine the relationship of community behavior in controlling the mosquito habitat with the presence of Aedes aegypti larvae in Dwikora. Methods: This research was an analytical survey with a cross-sectional design. The population in the present study was the patriarch or head of household residing at Dwikora sub-district, the total number of households was 452. By employing purposive sampling technique, 82 households were selected as samples. The data was collected by using the observation sheet and standardized questionnaire. Univariate and bivariate tests were performed for data analysis. Results: The results showed that there were 44 households which had less practice in mosquito habitat control, 48 households had a positive attitude, and 38 households had good knowledge. Bivariate analysis using chi-square test showed that there was a significant correlation between the household practice (p-value = 0.01) with the presence of Aedes aegypti larvae in Dwikora. Conclusion: It may indicate that the communities in Dwikora carry out less control over the existence of Aedes aegypti larvae at their houses. Therefore, it is suggested for the households to pay more attention to house cleanliness, to always use a closed bucket, apply abate to stagnant water and eradicate mosquito habitats periodically to avoid the occurrence of transmission of dengue hemorrhagic fever (DHF)